2017
DOI: 10.4336/2017.pfb.37.91.1337
|View full text |Cite
|
Sign up to set email alerts
|

The Spanish National Forest Inventory: history, development, challenges and perspectives

Abstract: É importante ter uma base de dados florestal estatisticamente robusta, que possa ser atualizada e possa fornecer informações em longo prazo. Os inventários florestais nacionais (IFN) fornecem uma das melhores fontes de informação de larga escala e, portanto, são a base para políticas florestais. O escopo dos IFNs, que são a principal fonte de dados para avaliações nacionais e de grandes áreas, foi ampliado para incluir novas variáveis, visando atender a crescentes requisitos de informação. Este artigo descreve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 7 publications
(9 reference statements)
0
26
0
Order By: Relevance
“…Since the Third SNFI3, forest area and strata estimation are described prior to the NFI using the National Forest Map . Although the primary objectives were the estimation of forest area and growing stock, the current aim of the SNFI is to provide information at national and regional levels about the state and evolution of forests through the analysis of growing stock, carbon pools, development of forest resources, forest health, risks and forest biodiversity (Alberdi et al 2017).…”
Section: National Forest Inventory (Nfi)mentioning
confidence: 99%
See 2 more Smart Citations
“…Since the Third SNFI3, forest area and strata estimation are described prior to the NFI using the National Forest Map . Although the primary objectives were the estimation of forest area and growing stock, the current aim of the SNFI is to provide information at national and regional levels about the state and evolution of forests through the analysis of growing stock, carbon pools, development of forest resources, forest health, risks and forest biodiversity (Alberdi et al 2017).…”
Section: National Forest Inventory (Nfi)mentioning
confidence: 99%
“…In Spain, due to the increasing national and international forest information requirements, the number of measured variables and objectives was broadened, including vertical structure. New methodologies were developed taking into consideration the national forest characteristics, the information requirements but also the National Forest Inventories harmonisation initiatives (Vidal et al 2016;Alberdi et al 2017…”
Section: Analysis Of the History And The Development Of The Nfi In Spmentioning
confidence: 99%
See 1 more Smart Citation
“…Trees with 2.5 ≤ dbh ≤ 7.5 cm were counted but not measured. For more details about the SNFI data, see Alberdi et al [34].…”
Section: Snfi Datamentioning
confidence: 99%
“…Thus, for example, Murgaš et al [41] reported that up to 10% of the plots had positioning errors of 20 m or more within inventories of selected management units in Slovakia. As revisiting SNFI plots to capture more accurate coordinates is very costly and time-consuming, Spanish authorities are planning to capture new coordinates with errors less than 1 m in the next re-measurement of SNFI plots [26,42], thus making it easier to combine the field plot data with the information provided by remote sensing systems [34].…”
Section: Harmonization Of Snfi and Als Datamentioning
confidence: 99%